Influence of pelletizing process parameters on the performance of V–Ti magnetite green pellets for composite agglomeration. (2nd January 2022) - Li, Zhan-Guo; Liu, Zheng-Jian; Zhang, Jian-Liang; Wang, Yao-Zu; Ma, Li-Ming; Niu, Le-Le; Xu, Chen-Yang; Wang, Gui-Lin
ABSTRACT: To use vanadium–titanium magnetite (VTM) resources for sintering, a composite agglomeration process (CAP) is applied. This paper studies the effects of pelletizing parameters, including particle size, moisture content and bentonite content on VTM green pellets, composite agglomeration process and mineralogy. The experimental results show that the optimal pellets particle size, water and bentonite content are 5–8 mm, 8.75% and 2.0%, respectively, for the strength of VTM pellets. In the sintering process, the economic and technical indexes obtained by using VTM pellets based on CAP are significantly better than those obtained by traditional sintering process. When using CAP, VTM pellets with the particle size of 5–8 mm have more advantages in the air permeability of the feed layer compared with those with the particle size of 10–12 mm, and accordingly have higher sintering speed, yield, productivity and lower fuel consumption. The addition of 15% ordinary magnetite concentrates into VTM pellets did not improve the productivity, but it was helpful to reduce the solid fuel consumption. By analysing the mineral phase structure of sintering products under different schemes, it is found that the pellets are closely bound to the matrix in the CAP. The main phase in the pellet part is hematite phase, and a large amount of SFCA phase can be observed in the matrix part. When ordinary magnetite concentrate is added, the crystal connections within the particles become more complete.